1990
DOI: 10.2307/1940253
|View full text |Cite
|
Sign up to set email alerts
|

Role of Enemy‐Free Space and Plant Quality in Host‐Plant Selection by Willow Beetles

Abstract: Phratora vitellinae and Galerucella lineola are two leaf beetles that feed on willows (Salix) in central Sweden. When disturbed, larvae of P. vitellinae exude droplets of a defensive secretion from dorsal glands. The secretion contains salicyl aldehyde, the precursors for which are plant—derived salicylates like salicin and other chemically similar phenolic glycosides. In contrast, larvae of G. lineola lack dorsal glands, cannot convert salicylates to salicyl aldehyde, and no not produce such a defensive secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
243
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(256 citation statements)
references
References 63 publications
10
243
3
Order By: Relevance
“…In two studies comparing caterpillars reared on the same plant, the specialist caterpillar was actually more vulnerable (Stamp 1992) and no relationship was found between host concentration of sequesterable compounds and host use by generalist or specialists in the presence of predators (Stamp and Bowers 2000). In the Phratora-Galerucella study cited previously, Denno et al (1990) compared a specialist and generalist on the same host, but did not directly asses their vulnerabilities to predation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In two studies comparing caterpillars reared on the same plant, the specialist caterpillar was actually more vulnerable (Stamp 1992) and no relationship was found between host concentration of sequesterable compounds and host use by generalist or specialists in the presence of predators (Stamp and Bowers 2000). In the Phratora-Galerucella study cited previously, Denno et al (1990) compared a specialist and generalist on the same host, but did not directly asses their vulnerabilities to predation.…”
Section: Discussionmentioning
confidence: 95%
“…Although this research has revealed a positive relationship between diet breadth and susceptibility to predator attack (Bernays and Graham 1988;Bernays and Cornelius 1989), it is not clear if the advantage of specialization derives from the characteristics of the insect species or from their host plants, since the specialists and generalists in all studies to date were collected or reared from different plant species. For example, among willow-feeding leaf beetles, Phratora vitellinae exudes defensive secretions derived from salicylate-rich willows upon which it specializes, whereas Galerucella lineola produces no such secretions but uses a wider variety of willow hosts (Denno et al 1990). Although the specialist is likely better protected, there was no direct assessment of susceptibility to predation for both species on the same host.…”
Section: Introductionmentioning
confidence: 99%
“…This creates a favourable opportunity for the population of E. clorana to avoid competition with other folivorous species, as well as its natural enemies. For E. clorana, the use of Spiraea tomentosa could therefore result in an enemy-free space (Denno et al 1990), which is potentially an important factor affecting host plant choice by phytophagous insects (Mulatu et al 2004). Utilising Spiraea tomentosa may also be beneficial for E. clorana as an opportunity to improve geographical and ecological expansion.…”
Section: Discussionmentioning
confidence: 99%
“…maximized given constraints. Some herbivores indeed show a positive correlation between adult oviposition preference and larval performance (Denno et al 1990). It has also been frequently found, however, that herbivorous insects use plants or plant parts on which larval performance is sub-optimal (Gratton and Welter 1999;Mulatu et al 2004).…”
Section: Enemy-free Spacementioning
confidence: 99%